HPLC determination of chlorhexidine gluconate and p-chloroaniline in topical ointment - Havlíková, L; Matysová, L; Nováková, L; Hájková, R; Solich, P (Journal of pharmaceutical and biomedical analysis, 2007)
A novel fast isocratic reversed-phase HPLC method for simultaneous determination of chlorhexidine and its degradation product p-chloroaniline was developed. Zorbax SB Phenyl column (75 mm x 4.6 mm, 3.5 microm) was used for the separation. Mobile phase composed of acetonitrile and buffer solution of 0.08 M sodium phosphate monobasic containing 5 ml of triethylamine (0.5%) and adjust with 85% phosphoric acid to pH 3.0 in ratio 35:65 (v/v) pumped isocratically at flow rate 0.6 ml min(-1) was used. UV detection was performed at 239 nm, the total analysis time was about 10 min. The method is suitable for practical routine analysis of topical ointment in the quality control laboratory.
Keywords: Chlorhexidine; Reproducibility of Results; acetonitrily; Hydrogen-Ion Concentration; Indicators and Reagents; Spectrophotometry, Ultraviolet; Quality Control; chlorhexidin; řízení kvality; aplikace lokální; reprodukovatelnost výsledků; indikátory a reagencie; Buffers; Veterinary Drugs; referenční standardy; Reference Standards; Ointments; vysokoúčinná kapalinová chromatografie; Aniline Compounds; spektrofotometrie ultrafialová; pufry; koncentrace vodíkových iontů; masti; veterinární léky; Administration, Topical; aniliny; Chromatography, High Pressure Liquid; Acetonitriles